2009
DOI: 10.1038/oby.2008.657
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Race/Ethnicity on the Relationship Between Visceral Fat and Inflammatory Biomarkers

Abstract: The purpose of this study was to determine whether racial/ethnic differences exist in the relationship between visceral adipose tissue (VAT) and selected inflammatory biomarkers. Subjects included 136 African‐American, 133 Hispanic, and 100 white men and women, aged ≥45. Waist circumference and BMI were measured using standard methods. Total VAT, and VAT and subcutaneous adipose tissue (SAT) at the L4L5 spinal level were measured using computed tomography. Interleukin‐6 (IL‐6), C‐reactive protein (CRP), and fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
85
2
3

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 103 publications
(99 citation statements)
references
References 44 publications
(58 reference statements)
6
85
2
3
Order By: Relevance
“…Consistent with this notion, although not found in all studies, 40,42,44 evidence suggests that waist circumference and waist-to-height ratio may be more valid than BMI across racial groups. For example, as described earlier, BMI differentially predicts all-cause mortality among African Americans versus European Americans; however, the same study demonstrated that waist circumference is a robust predictor among both races.…”
Section: Gillespie and Christiansupporting
confidence: 63%
See 1 more Smart Citation
“…Consistent with this notion, although not found in all studies, 40,42,44 evidence suggests that waist circumference and waist-to-height ratio may be more valid than BMI across racial groups. For example, as described earlier, BMI differentially predicts all-cause mortality among African Americans versus European Americans; however, the same study demonstrated that waist circumference is a robust predictor among both races.…”
Section: Gillespie and Christiansupporting
confidence: 63%
“…39 Thus, it is notable that prior studies have shown that at similar or even lower BMI, European Americans exhibit greater visceral adiposity than African Americans. [40][41][42][43] Moreover, when evaluated as a linear relationship, BMI is more strongly associated with visceral adiposity among European Americans than African Americans. 44 Thus, measures that capture central adiposity may provide better or complementary information.…”
Section: Gillespie and Christianmentioning
confidence: 99%
“…Briefly, study participants were recruited from the general population and primary care clinics through the NorTex network (www.hsc.unt.edu/ Nortex), using either public advertisement or physician's referral. [25][26][27] The inclusion criteria include (1) males and females over the age of 45, (2) being Caucasian, Hispanic or African American and (3) no current or previous self-reported history of stroke, peripheral arterial disease, renal failure, heart failure or coronary heart disease and cancer.…”
Section: Methodsmentioning
confidence: 99%
“…Data on ethnic differences in IL-6 and TNF-a are more limited. Some studies found higher concentrations of IL-6, 40 but similar levels of TNF-a 41 in individuals of African compared with European ancestry. Our study only focused on African ancestry individuals, and it is not possible to compare our values with these other studies due to assay differences and differences in cohort characteristics.…”
Section: Miljkovic Et Almentioning
confidence: 99%